The Importance of Individual-Site and System-Wide Community Health Needs Assessments - Bias, Thomas; Abildso, Christiaan; Sarkees, Emily (Frontiers in Public Health, 2020)
In order to fulfill the Patient Protection and Affordable Care Act's Community Health Needs Assessment requirements, hospital systems sometimes vary in detail between individual hospital sites or locations and performing an assessment for the entire system. This article examines needs assessments and their accompanying implementation plans across a large university hospital system and finds support for conducting assessments at the local site-level but evidence that system-wide approaches may also have significant benefits, especially at the implementation phase. It suggests a hybrid approach to the needs assessment process where systems and their individual hospitals work together to maximize health benefits to the communities served.